Prevention of the mouth cancer in the community - Yanei Laplana de la Torre; José Luis Cadenas Freixas (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Introduction: The paper was carried out with the objective to characterize the situation in the process of prevention of the mouth cancer in the Clinic Arturo Puig Ruiz de Villa, of the Minas municipality, in the Camagüey province, Cuba. Method: The study is a part of one of the actions of a research project of community character that is executed in the period understood from January, 2019 and December, 2020. Results: It exhibits the observation of the relation between the natural conditions of the community, its customs and familiar and social practices with the risk factors that propitiate the appearance of the mouth cancer. The results appear in charts and the theoretical and methodological foundation comes from the documentary review of diverse printed sources and databases recognized in the field of the medical sciences. Discussion: The subject-matter is of supreme interest in the current studies in the Cuban, Latin-American and world context as it was stated in the different consulted sources.